2021
DOI: 10.1155/2021/9491376
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation of Remote Sensing Image Based on GAN and FCN Network Model

Abstract: Accurate remote sensing image segmentation can guide human activities well, but current image semantic segmentation methods cannot meet the high-precision semantic recognition requirements of complex images. In order to further improve the accuracy of remote sensing image semantic segmentation, this paper proposes a new image semantic segmentation method based on Generative Adversarial Network (GAN) and Fully Convolutional Neural Network (FCN). This method constructs a deep semantic segmentation network based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…is method involves obtaining labeled images and unlabeled images, which improves the accuracy of image semantic segmentation model. Tian et al [20] proposed a method to obtain the sample image of the enhanced image and fuse it. rough the fused image, the semantic segmentation image is obtained by using the semantic segmentation model.…”
Section: Relevant Research Workmentioning
confidence: 99%
“…is method involves obtaining labeled images and unlabeled images, which improves the accuracy of image semantic segmentation model. Tian et al [20] proposed a method to obtain the sample image of the enhanced image and fuse it. rough the fused image, the semantic segmentation image is obtained by using the semantic segmentation model.…”
Section: Relevant Research Workmentioning
confidence: 99%
“…In addition, it also allowed the gradient to spread directly toward any convolutional layer and the introduced attention mechanism obtained weighted high-level features, which was conducive to extracting global contexts and more effective semantic information, thereby better preserving the edges, texture, and other information of images and improving segmentation performance. For the ISPRS Potsdam dataset, the FPS of our method is 25, which is better than Tian et al (2021) and close to Chen et al (2020). It is shown that the proposed method can improve the segmentation accuracy while ensuring the computational efficiency.…”
Section: Isprs Potsdam Datasetmentioning
confidence: 81%
“…Using the method in Chen et al (2020), the OA was 0.871, the F1 was 0.883, and the MIoU was 0.671. Using the method in Tian et al (2021), the OA was 0.872, the F1 was 0.884, and the MIoU was 0.723. This showed that the proposed method not only integrated more original input information for this layer but also enhanced feature fusion by connecting the complete long-distance and short-distance residuals.…”
Section: Isprs Potsdam Datasetmentioning
confidence: 99%
“…et al, 2021;Seong and Choi, 2021). Later, Transformer-based and generative adversarial network (GAN) methods no doubt are getting more and more attention (Shamsolmoali et al, 2020;Tian et al, 2021;Cui L. et al, 2022;He et al, 2022;Wang L. et al, 2022).…”
Section: Introductionmentioning
confidence: 99%